The Studies Qualitative about Incident Stunting in Toddlers Age 0 – 6 in Medan Belawan District - Helfrida Situmorang; Wilda Yunita; Maimunah (PT Inovasi Pratama Internasional, 2022)
Study this conducted for describe about incident stunting in toddlers aged 0-6 years in Medan Belawan District , Medan City , North Sumatra Province . Problem child short ( stunting ) is one problem nutrition faced in the world, especially in poor and developing countries . Based on results and discussion research , then could concluded that many experienced child stunting in Medan Belawan sub -district, Medan City , North Sumatra Province because a number of factor that is lack of deep parental knowledge Thing this is mothers and cadres Integrated Healthcare Center about issue stunting that alone . Society especially moms reluctant for attend counseling about issue stunting with reason busy . So that they no understand about MP-ASI because a number of mother already introduce child with MP-ASI even at a very old age early . Besides because lack of knowledge , height number stunting is also caused by conditions economy society that can said low so that not enough capable for Fulfill all needs nutrition child and mother .